Kunsthalle Lophem : Projecten 1998. - Debruyne, Johan; Demeester, Ann; Geirlant, Piki; Holthof, Marc; Ké, J.; Milkers, Anne; Patteeuw, Roland; Polegato, Lino; Roelandt, Els; Wahjudi, Claudia; Willaert, Philip (Loppem : Kunsthalle Lophem v.z.w. Center for Contemporary Art, 1999)
Moulène, Jean-Luc ; Geys, Jef ; Roudenko-Bertin, Claire ; Wool, Christopher ; Van Kerckhoven, Anne-Mie ; Burki, Marie José ; Geys, Jef ; Hyber, Fabrice ; Potter, Carter ; Serebriakova, Maria (Marsha) ; Airo, Mario ; Goethals, Marc ; d'O, Honoré ; Colpaert, Eric ; Valldosera, Eulàlia ; Pacquée, Ria ; Huyghe, Philip ; Ondreicka, Boris ; de Zeeuw, Mirjam
persdossier
overzicht projecten 1998
Nederlands & Duits
boek